2013
DOI: 10.1111/php.12158
|View full text |Cite
|
Sign up to set email alerts
|

Association of Valdecoxib, a Nonsteroidal Anti‐Inflammatory Drug, with Human Serum Albumin

Abstract: Valdecoxib addition quenches the intrinsic human serum albumin (HSA) fluorescence. This allows an evaluation of the drug-protein association. However, both the number of binding sites and their affinity for the drug depend upon the methodology employed for their evaluation and the employed protein concentration. In this work, we measured the effect of valdecoxib on HSA fluorescence yield over a wide range of experimental conditions and discuss the validity of the binding parameters derived from the different d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In the light of the importance of the binding properties of HSA, much crystallographic and spectroscopic data on HSA:drug complexes has been reported in the literature, and many efforts have been performed to correctly determine the number of binding sites. , Moreover, several studies in solution were focused on the stabilizing effect of ligand binding on the protein structure. To highlight similar stabilizing effects, we recently reported a structural and spectroscopic combined study on the unfolding pathway of HSA binding ibuprofen (Ibu), a nonsteroidal anti-inflammatory drug . As an extension of this study, in this work, the urea-induced unfolding of HSA in complex with two drugs is reported.…”
Section: Introductionmentioning
confidence: 92%
“…In the light of the importance of the binding properties of HSA, much crystallographic and spectroscopic data on HSA:drug complexes has been reported in the literature, and many efforts have been performed to correctly determine the number of binding sites. , Moreover, several studies in solution were focused on the stabilizing effect of ligand binding on the protein structure. To highlight similar stabilizing effects, we recently reported a structural and spectroscopic combined study on the unfolding pathway of HSA binding ibuprofen (Ibu), a nonsteroidal anti-inflammatory drug . As an extension of this study, in this work, the urea-induced unfolding of HSA in complex with two drugs is reported.…”
Section: Introductionmentioning
confidence: 92%
“…These curves show negative deviation from linearity, mainly in the higher concentration range of indomethacin, and concave towards the x-axis. This phenomenon usually happens when there is more than one tryptophan residue with a distinct environment and different accessibility to the quencher [ 45 , 49 , 50 ], but it is well known that HSA has only one tryptophan residue located in the subdomain IIA, thus, there is a possibility of the existence of more than one binding site for indomethacin inside HSA [ 51 ], and the larger distance of secondary binding site in comparison to the primary one reduced the quenching efficiency, thus, a negative deviation in the Stern–Volmer plots could be expected [ 52 , 53 , 54 ]. Silva and coworkers have suggested that the binding of a ligand to the HSA may lead to the possible conformational change followed by the exposition of lower affinity binding sites [ 55 ].…”
Section: Resultsmentioning
confidence: 99%